Analysis of microparticle resuspension in turbulent flows with horizontally vibrating surface - Nakorn Tippayawong (2018)
Removal of deposited particles is a key issue in particulate contamination control in hard disk assembly. Successful resuspension predictions require a good knowledge of forces for microparticles deposited on rough surfaces. This work is about removal of particles in turbulent air flow with external excitation. A well known, kinetic detachment model was modified and applied to the resuspension of particles. The modified model was derived from the energy accumulation approach with combined aerodynamic drag and in-plane vibration to separate particles from a surface. Moments of adhesion, aerodynamic drag, and vibration acting on microparticles deposited to the surface were evaluated. An expression was obtained for the resuspension rate from surfaces where a spread of adhesive forces due to surface roughness was taken into consideration. The prediction results showed similar qualitative and quantitative trends to the experimental results from the literature. Frequency of particle-surface interaction was found to significantly influence the removal rate of microparticles from the surface.